Antecedents and consequences of workplace violence against nurses: A qualitative study. Issue 1 (17th July 2017) - Najafi, Fereshteh; Fallahi‐Khoshknab, Masoud; Ahmadi, Fazlollah; Dalvandi, Asghar; Rahgozar, Mehdi
Abstract : Aims and objectives: To explore Iranian nurses' perceptions of and experiences with the antecedents and consequences of workplace violence perpetrated by patients, patients' relatives, colleagues and superiors. Background: Workplace violence against nurses is a common problem worldwide, including in Iran. Although many studies have reviewed the antecedents and consequences of workplace violence, limited information is available on this topic. An understanding of the predisposing factors for violence and the consequences of violence is essential to developing programs to prevent and manage workplace violence. Design: Qualitative descriptive design. Methods: In this qualitative study, 22 unstructured, in‐depth interviews were conducted with registered nurses who had experienced workplace violence and who were selecting using purposive sampling in nine hospitals. Inductive content analysis was used to analyse the data. Results: Five categories emerged as predisposing factors: unmet expectations of patients/relatives, inefficient organisational management, inappropriate professional communication, factors related to nurses and factors related to patients, patients' relatives and colleagues. Individual, familial and professional consequences were identified as outcomes of workplace violence against nurses. Conclusions: Workplace violence by patients/their relatives and colleagues/superiors is affected by various complicated factors at the individual and organisational levels. In addition to negatively affecting nurses' individual and family lives, workplace violence may lead to a lower quality of patient care and negative attitudes towards the nursing profession. Relevance to clinical practice: Identifying factors, which lead to workplace violence, could help facilitate documenting and reporting such incidents as well as developing the necessary interventions to reduce them. Furthermore, native instruments must be developed to predict and monitor violence.